Remifentanil Patient-controlled Analgesia in Labour: 6-Year Audit of Outcome Data of the RemiPCA SAFE Network (2010-2015). Issue 2 (June 2020) - Melber, A.A.; Jelting, Y.; Huber, M.; Keller, D.; Dullenkopf, A.; Girard, T.; Kranke, P.
Abstract : ( Int J Obstet Anesth . 2019;39:12–21) Remifentanil patient-controlled analgesia (PCA) has been used for ∼20 years during labor as an alternative analgesic approach. While many units utilize this analgesic option in patients who cannot receive neuraxial analgesia, some offer it routinely to their laboring patients. There are some potentially serious side effects of remifentanil PCA, such as respiratory depression and hypoxemia. Swiss researchers developed the RemiPCA SAFE Network in 2009 when the analgesic technique became available in their country. The purpose of the network was to monitor PCA use and assess maternal and neonatal outcomes. While initially developed for Swiss facilities, the network later allowed obstetric units from other countries to participate and provide their data. Data collected by the network helps individual facilities to evaluate their performance and allows the network committee to assess the overall outcomes of remifentanil PCA for labor. The goal of the current audit study was to accurately outline the quality assurance system used by the network and analyze outcomes on remifentanil PCA effectiveness and safety based on the data collected.